Investigation and Restoration of BEST1 Activity in Patient-derived RPEs with Dominant Mutations - Ji, Changyi (Sci Rep, 2019)
BEST1 is a Ca(2+)-activated Cl(−) channel predominantly expressed in retinal pigment epithelium (RPE), and over 250 genetic mutations in the BEST1 gene have been identified to cause retinal degenerative disorders generally known as bestrophinopathies. As most BEST1 mutations are autosomal dominant, it is of great biomedical interest to determine their disease-causing mechanisms and the therapeutic potential of gene therapy. Here, we characterized six Best vitelliform macular dystrophy (BVMD)-associated BEST1 dominant mutations by documenting the patients’ phenotypes, examining the subcellular localization of endogenous BEST1 and surface Ca(2+)-dependent Cl(−) currents in patient-derived RPEs, and analyzing the functional influences of these mutations on BEST1 in HEK293 cells. We found that all six mutations are loss-of-function with different levels and types of deficiencies, and further demonstrated the restoration of Ca(2+)-dependent Cl(−) currents in patient-derived RPE cells by WT BEST1 gene supplementation. Importantly, BEST1 dominant and recessive mutations are both rescuable at a similar efficacy by gene augmentation via adeno-associated virus (AAV), providing a proof-of-concept for curing the vast majority of bestrophinopathies.